2020
DOI: 10.1016/j.cemconres.2020.106141
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale micromechanical analysis of alkali-activated fly ash-slag paste

Abstract: Current demand for highly sustainable concrete, e.g. alkali-activated fly ash-slag (AAFS) concrete, urges understanding the links between microstructure and micromechanical properties of this binder. This paper presents a systematic investigation into the microstructure and micromechanical properties of AAFS paste from nanoscale to micro-scale. Nanoindentation was used to evaluate the micromechanical properties, while the microstructure was characterised using 29 Si nuclear magnetic resonance, Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(30 citation statements)
references
References 100 publications
(191 reference statements)
2
28
0
Order By: Relevance
“…MPa, which was increased by 132.1% and 155.8% at 7 and 28 d, respectively. With the increase of PVA fibre content from 1.5 vol% to 2 vol%, the compressive strength of SHGC was improved by 34.7% at 1 d but slightly reduced by 9.7% and 7.3% at 7 and 28 d. The increase of compressive strength with increasing fibre content at early age can be ascribed to the more energy of fracture required to pull fibres out[70]. However, this effect could be altered by the inadequate compaction of SHGC specimens, leading to an increase of porosity and decrease of strength.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…MPa, which was increased by 132.1% and 155.8% at 7 and 28 d, respectively. With the increase of PVA fibre content from 1.5 vol% to 2 vol%, the compressive strength of SHGC was improved by 34.7% at 1 d but slightly reduced by 9.7% and 7.3% at 7 and 28 d. The increase of compressive strength with increasing fibre content at early age can be ascribed to the more energy of fracture required to pull fibres out[70]. However, this effect could be altered by the inadequate compaction of SHGC specimens, leading to an increase of porosity and decrease of strength.…”
mentioning
confidence: 93%
“…displays the effect of hybrid fibre content on compressive strength of SHGC at 1, 7 and 28 d. In general, the compressive strength of all mixtures increased gradually with increasing curing age due to the geopolymerisation process. SHGC containing 1.5 vol% PVA fibre had a 1-d compressive strength of 13.1 attributed to the high stiffness and hydrophilicity nature of RTS fibre, which can absorb more energy and provide strong fibre-matrix interaction[24,66,70].Regarding the hybrid fibre system of SHGC specimens, the partial RTS fibre replacement of PVA fibre showed various effects on compressive strength at different ages. At the early ages (1 and 7 d), the replacement level of RTS fibre had a marginal effect on compressive strength of SHGC specimens,whereas a clear trend at 28 d indicated that the compressive strength increased with the replacement of RTS fibre.…”
mentioning
confidence: 99%
“…The wide, low-resolution signals in the right-side area of the spectrum were due primarily to unreacted FA. Q 4 (mAl) (m = 4, 3, 2, 1 or 0) units also found in this zone were attributed to Ca 2 + -low N-A-S-H and (N,C)-A-S-H gels (N-(C)-A-S-H-like gels) [98,102,103], characterized by a highly polymerized aluminosilicate structure in which Si and Al were tetrahedrally coordinated. The signals at around −93 ppm were associated with Q 4 (3Al) signals generated by N-A-S-H gels with reactive and highly polymerized aluminate phases.…”
Section: Samplementioning
confidence: 64%
“…The Q 4 (2Al) units located at around −97 ppm and Q 4 (1Al) units at around −103 ppm were the most stable Si-high N-A-S-H sites. The signals at −105 ppm and −116 ppm were attributed to Q 4 (0Al) units associated with the presence of the crystalline quartz phases in fly ash [86,102,104].…”
Section: Samplementioning
confidence: 99%
“…The soluble silicates in the activator seem to restrict the moisture transportation in the pore structure. The geopolymers activated with sodium silicate generally have more compact pore structures than the geopolymers activated with sodium hydroxide [17][18][19]. This is helpful in slowing down the movement of free alkalis in the matrix.…”
Section: Testing and Characterizationmentioning
confidence: 99%